Protecting Children’s Rights in Foster Care: Evaluating Legal Standards and Challenges - Eszter Kovács; Gábor Nagy (International Journal of Social Welfare and Family Law, 2024)
This article examines the legal protections in place for children in foster care systems, focusing on issues such as stability, mental health support, and legal representation. By reviewing foster care policies in several countries, the study assesses how well these policies uphold children's rights and meet their emotional and developmental needs. Findings reveal gaps in foster care protections, suggesting that more consistent standards are necessary to ensure children's welfare.